PHARMACEUTICAL ANALYTICAL STUDY OF KAMPAVATARI RASA - AN AYURVEDIC HERBO MINERAL FORMULATION - Rohan, Patil; Reshma Prakash, *Yaranal; Pallavi, Dindore (International Journal of Ayurveda and Pharma Research, 2016)
Kampavatari Rasa (KVR) is a unique Ayurvedic herbo- mineral formulation mentioned in the classics Rasa Raj Sundar in Vata vyadhi and indicated mainly in Kampavata which resembles Parkinson's disease. The line of treatment in Ayurveda is to combat Vata dosha and to sustain neuronutrition by Rasayana remedies, which can be achieved by Kamapavatari Rasa with its properties like Tridosh shamaka and Rasayana. The present study was executed to establish a finger print for this unique formulation which can be used further for drug standardization. Kampavatari rasa is prepared by triturating Tamra bhasma and Rasa Sindura in equal quantity with Katuki swaras (Picrohiza kurroa) for 21 times. Each ingredient was prepared according to the norms of Ayurvedic classical texts. Raw drugs were selected on bases of Grahya lakshana and its percentage. To ensure the proper preparation of Tamra bhasma, standard tests (Bhasma Pariksha), XRD, NPST and SEM were carried and for Rasa sindura NPST test and XRD were employed. After been complied these tests KVR was prepared and subjected for physico chemical analysis and quantitative analysis of Mercury, Sulphur and Copper by ICPAES. The study of Kampavatari Rasa revealed that its Loss on Drying - 3.4%, Total Ash - 48 %, Acid insoluble ash -13%, water soluble ash - 9.5%, Hardness test was 7kg/cm2 and Tablet disintegration test 14/min which are within the normal limits and ICP – AES shows the percentage of Copper 20.51, Sulphur 8.9, and Mercury 20.43. This is the first study to establish the characterization of Kampavatari rasa.